Rent-Sharing and Collective Bargaining Coverage: Evidence from Linked Employer-Employee Data - Nicole Gürtzgen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Using a linked employer-employee data set, this paper analyses the relationship between firm-profitability and wages. Particular emphasis is given to the question of whether the sensitivity of wages to firm-specific rents varies with collective bargaining coverage. To address this issue, we distinguish sector- specific wage agreements, firm-specific wage agreements and wage determination without any bargaining coverage. Our findings indicate that individual wages are positively related to firm-specific rents in the non-union sector and under firm-specific contracts. Industry-wide wage contracts, however, seem to suppress firm-level rent-sharing. While pooled OLS estimates yield a positive correlation between wages and quasi-rents under centralised contracts, estimates accounting for unobserved individual and establishment heterogeneity point to a coe? cient of zero. Differenced GMM estimates accounting for the endogeneity of our profitability measure even point to a negative relationship under centralised contracts.
More recent version: http://hdl.handle.net/10419/24699
Keywords: C23; J51; J31; 330; Rent-Sharing; Unions; Linked Employer-Employee Data; Lohnbildung; Rentabilität; Lohnverhandlungstheorie; Rententheorie; Tarifpolitik; Schätzung; Deutschland